Effect of pretreatment conditions on the catalytic activity of nano-sized TPA/ZrO2 dispersed in SBA-15 channels in acetylation reactions - Sawant, Dhanashri P.; Hartmann, Martin; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2007)
Acetylation of an aromatic compounds such as veratrole (1,2-dimethoxybenzene), anisole, thioanisole, isobutyl benzene and 2-methoxynaphthalene with acetic anhydride has been investigated over a nano-sized 12-tungstophosphoric acid (TPA)/22.4 wt.%ZrO2/SBA- 15 catalysts in the liquid phase conditions. Catalysts with different (%) TPA and zirconia loadings calcined at different temperatures were prepared by wet-impregnation and characterized by XRD, N-2 adsorption-desorption, FT-Rarnan, X-ray photoelectron spectroscopy (XPS). The acidic behavior of the catalyst was studied by TPD of ammonia and FT-IR pyridine adsorption. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/SBA- 15 calcined at 1123 K had the highest acidity and was the most active catalyst in veratrole acetylation with acetic anhydride. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: acetylation; SBA-15; TPA/ZrO2; veratrole; wet-impregnation

Electrostatic grafting of a triphenylphosphine sulfonate on SBA-15: application in palladium catalyzed hydrogenation - Wang, Lei; Dehe, Daniel; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Zhou, Zhou; Hartmann, Martin; Taylor, Robin N. Klupp; Singh, Anand Pal; Jia, Mingjun; Thiel, Werner R. (Catalysis Science & Technology, 2012)
A novel strategy for the immobilization of a sulfonate functionalized triphenylphosphine ligand by ion-ion interactions on an imidazolium modified SBA-15 is presented. A support containing electrostatically grafted triphenylphosphine as the ligand was reacted with PdCl2( CNPh)(2) and the resulting hybrid material catalyzed olefin hydrogenation under mild conditions. The catalyst exhibits excellent activity, selectivity and stability and it can be reused for at least ten times without any loss of activity. An analogous but covalently grafted palladium system does not show any hydrogenation activity under the same conditions. TEM images of the used catalyst clearly prove the absence of palladium nanoparticles. Additionally, XPS investigations prove that palladium( 0) is formed and the phosphine is oxidized. By AAS no palladium contamination down to 0.5 X 10(-4) mmol could be detected in the products and further leaching tests verified the reaction to be truly heterogeneous. This concept of non-covalent immobilization guarantees a tight bonding of the catalytically active species to the surface in combination with a high mobility, which should be favorable for other catalyses, too.